Exploring the Implementation of Digital Marketing Strategies in Non-Formal Educational Institutions - Anggoro Panji Nugroho; Dessyana Kardha; Joko Rochmadi; Sachin Gupta (Universitas Negeri Semarang, 2024)
Marketing is one of the efforts that can be done in order to remain competitive with competitors, efforts to achieve predetermined goals, and in response to changes in a dynamic and competitive environment. Digitalization and the internet are changing traditional forms of marketing into modern marketing or called digital marketing. Digital marketing utilizes digital technology as a means in the online marketing process, so that it can reach wider online users. Non-formal educational institutions provide education, training and development services to the community and operate as non-profit organizations. Digital marketing carried out by non-formal educational institutions in Semarang is a response to the opportunities for educational institutions to show their potential, so that they can attract students or parents because of their advantages. This study aims to examine the application of digital marketing in non-formal educational institutions, including the objectives, advantages, and digital marketing media used using a descriptive qualitative research approach. The study population was determined by all non-formal educational institutions in Semarang which amounted to 83. The entire population was included in the study sample. Data collection was carried out using observation, documentation, and questionnaire methods. The results showed that the purpose of digital marketing is as an effort to expand information on educational program services provided as well as for the recruitment of new students. Various benefits are obtained through digital marketing, such as wider and faster user reach, permanent content, and lower costs. Non-formal educational institutions in Semarang prefer to use digital marketing media (free and paid) in accordance with the growing trends and their frequent use, such as Facebook and Instagram. Non-formal educational institutions in Semarang tend to avoid high-paying digital marketing media due to budget constraints.